The potential applications of peptide-loading complex in cancer treatment - Song, Zhidu; Tao, Ying; You, Jiaxin (Frontiers in Immunology, 2025)
Immunotherapy for cancer has made significant strides in the last several years. The prognosis for cancer patients has significantly improved as a result, particularly in hematological diseases. However, it was discovered that translating these achievements to solid tumors proved challenging. The peptide-loading complex (PLC), a temporary multisubunit membrane assembly in the endoplasmic reticulum (ER), is crucial for initiating a hierarchical immune response. Chaperones calreticulin and tapasin make up the PLC, unique to class I glycoproteins, thiooxido-reductase ERp57, and a transporter associated with antigen processing. The loading and editing of major histocompatibility complex class I (MHC-I) molecules with peptide translocation into the ER are synchronized by the PLC. One of the immune escape strategies revealed for tumors so far is changes in the expression of MHC molecules. This is because MHC antigens are crucial in presenting antigens to T-lymphocytes and controlling NK cell activity. Furthermore, decreased MHC-I expression has been linked to malignancies resistant to T-cell-based cancer immunotherapies (adoptive transfer of antitumor CD8 T-cells or checkpoint inhibition). The PLC is essential for T-cell priming, differentiation, and tumor growth control because it can bind to a wide range of MHC-I allomorphs. In this review, we have looked into PLC’s function and effects in all forms of cancer to improve cancer therapy techniques.